Penal culture and hyperincarceration : the revival of the prison - Cunneen, Chris, 1953- (Advances in criminology., 2013)
Using penal culture as a conceptual and theoretical vehicle, and Australia as a case study, this book analyses international developments in penality and imprisonment. Authored by some of Australia's leading penal theorists, the book examines the historical and contemporary influences on the use of the prison, with analyses of colonialism, post colonialism, race, and what they term the 'penal/colonial complex', in the construction of imprisonment rates and on the development of the phenomenon of hyperincarceration. Comparative, contemporary and historical in its approach, the book provides a n.